PRINSIP PENYUSUNAN ESTETIKA BENTUK DAN FASADE PADA BANGUNAN BANK INDONESIA, YOGYAKARTA - Nurdiansyah, Dian; Widiyanti (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2020)
Bank Indonesia Yogyakarta is a historical heritage building, a culturalheritage that tells of the nobility of a society, historical relics that are scatteredthroughout the Indonesian archipelago, one of which is the city of Yogyakartawhich is a building that must be preserved and preserved. stands out in his city asan icon of historical heritage. but over time the building was converted into alibrary. This study aims to examine the principles of the aesthetic formulation offorms and facades. This research uses a descriptive qualitative method